2016
DOI: 10.1186/s12864-016-3239-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs regulate gene plasticity during cold shock in zebrafish larvae

Abstract: BackgroundMicroRNAs (miRNAs) are critical regulators responding to acute environmental stresses in both plants and animals. By modulating gene expression, miRNAs either restore or reconstitute a new expression program to enhance cell tolerance to stresses. Cold shock is one of the stresses that can induce acute physiological responses and transcriptional changes in aquatic creatures. Previous genomic studies have revealed many cold-affected genes in fish larvae and adults, however, the role of miRNAs in acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…We characterised the network of protein-protein interactions (PPI) that indicated all studied proteins have functions related to the vertebrate circadian system, as they interact with core circadian proteins (supplementary table S3). Interestingly, we found that most PER and CRY proteins of Squalius interact with BHLHe41 (basic helix-loop-helix family, member e41), a protein associated with biochemical pathways activated in response to cold temperatures, as previously observed in cold shock responses in zebrafish larvae (Hung et al 2016).…”
Section: Identification and In Silico Characterisation Of Circadian-rsupporting
confidence: 74%
“…We characterised the network of protein-protein interactions (PPI) that indicated all studied proteins have functions related to the vertebrate circadian system, as they interact with core circadian proteins (supplementary table S3). Interestingly, we found that most PER and CRY proteins of Squalius interact with BHLHe41 (basic helix-loop-helix family, member e41), a protein associated with biochemical pathways activated in response to cold temperatures, as previously observed in cold shock responses in zebrafish larvae (Hung et al 2016).…”
Section: Identification and In Silico Characterisation Of Circadian-rsupporting
confidence: 74%
“…In the literatures, the family of miR-29 was found to respond to environmental stress and cellular repairing processes. In zebrafish model, the involvement of miR-29 in acute environmental stress (cold stress) was studied [39], in which the miR targeted on a core clock gene per2 to enhance cold tolerance of the fish larvae. Moreover, miR-29b was reported to play a role in cell regeneration, associated with the processes of cell survival and cytoskeleton reorganization in zebrafish [40].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in agreement with results from Danio rerio and other sh species [20,21,37,38] (summary on Table S1), we detected possible diversi cation in functions of the circadian genes that may have arisen to optimize important biological processes, synchronised with the circadian oscillation. We found that in Squalius the set of predicted protein-protein interactions in CRY, PER and BMAL (Table S3) involve circadian related proteins, but also proteins with other biological functions, namely BHLHe41 (basic helixloop-helix family, member e41) and HSF2 (heat-shock factor 2), involved in temperature response [22,[39][40][41], or with NFIL3-5 (nuclear factor, interleukin 3-regulates, member 5), a protein involved in immune response [42].…”
Section: Identi Cation Of Paralogs and Orthologs Of All Circadian Genmentioning
confidence: 99%